Content Preference among Online and Hardcopy Newspaper Readers in Imo State - Ashong, Ashong C; Henry, Ogaraku C (Journal of New Media and Mass Communication, 2017)
The emergence of newspapers online has created an ambivalence globally. Whereas the general feeling is that the online version of newspapers are a threat to the print’s business model, it is difficult to tell between online version and hardcopy newspapers which one is more economically rewarding as both are readily available and appear to thrive at least in Nigeria. This study is a survey of 392 newspaper readers in Imo State, selected in accordance with the Taro Yamane formula. Findings show that 80% of the respondents read both versions of newspapers, and that content is immaterial as a determinant of preferred version (76%). Rather, availability accounts for the version attended to per time. In addition, certain demographic and psychographic factors influence choice of content as well as media. It is therefore recommended among other things that the newspaper industry strive to provide both online and print versions provided that appropriate emphasis is laid on news which respondents consider the most valuable of newspaper contents.